Prudence, Emotional State, Personality, and Cognitive Ability - Breaban, Adriana; van de Kuilen, Gijs; Noussair, Charles N. (Frontiers in Psychology, 2016)
We report an experiment to consider the emotional correlates of prudent decision making. In the experiment, we present subjects with lotteries and measure their emotional response with facial recognition software. They then make binary choices between risky lotteries that distinguish prudent from imprudent individuals. They also perform tasks to measure their cognitive ability and a number of personality characteristics. We find that a more negative emotional state correlates with greater prudence. Higher cognitive ability and less conscientiousness is also associated with greater prudence.